Human and animal brucellosis in the Sultanate of Oman: an epidemiological study - Falah Al-Ani; Said Al Ghenaimi; Emad Hussein; Julanda Al Mawly; Khalid Al MushaiKi; Salim Al Kathery (Journal of Infection in Developing Countries)
Introduction: Brucellosis is an infectious disease caused by direct contact with infected animals or animal products contaminated with Brucella. Brucella is a Gram-negative aerobic coccobacillus that infects different types of animals and is considered to be an important zoonotic disease.